Integration of a vertical voluntary medical male circumcision program into routine health services in Zimbabwe: A solution for sustainable HIV prevention. - Amanda Marr Chung; Joseph Murungu; Precious Chitapi; Rudo Chikodzore; Peter Case; Jonathan Gosling; Roly Gosling; Sinokuthemba Xaba; Getrude Ncube; Owen Mugurungi; Patience Kunaka; Stefano M Bertozzi; et al. (PLOS Global Public Health, 2025)
The global health community has recognized the importance of integrating and sustaining health programs within national health systems rather than managing stand-alone 'vertical' interventions. Corresponding with these objectives, international aid donors are embracing the principle of localization. Voluntary Medical Male Circumcision (VMMC) in Zimbabwe is a large vertical HIV prevention program that was primarily funded through development assistance for health. Program stakeholders want to sustainably integrate VMMC into routine health services so that the program will continue to be a cost-effective HIV prevention strategy. The research team studied the effectiveness of a district-level intervention to empower local stakeholders in this integration effort. To evaluate this intervention, the research team conducted a document review of district-level work plans, combined with a survey administered to district teams assessing sustainability capacity of the program. Over a two-year period, Task Teams in all five intervention districts successfully integrated the VMMC program by reducing barriers and leveraging opportunities in other parts of the health system. Key outcomes impacted all WHO health system building blocks, including enhanced leadership and governance, improved service delivery through better access and acceptability, an expanded health workforce through training, more efficient use of medical technologies, improved data quality, and the mobilization of local funds to support program financing and sustainability. The sustainability survey showed a reduction in funding stability but a significant increase in communications, program adaptation, and organizational capacity. By institutionalizing participatory work planning, fostering local ownership, and mobilizing resources, the project demonstrated a successful model for integrating, scaling, and sustaining VMMC services. Other health programs in low- and middle-income countries seeking to integrate and sustain health services at subnational levels should consider this diagonal, bottom-up model to promote local leadership development and health system strengthening.